2009
DOI: 10.1080/13102818.2009.10818451
|View full text |Cite
|
Sign up to set email alerts
|

The Determination of Colour Intensity ofRubia TinctorumandChrozophora TinctoriaDistributed in Western Anatolia

Abstract: The aim of this study is to determinate the colour intensity of Rubia tinctorum L., Rubiaceae (dyer's madder) and Chrozophora tinctoria (L.) A. Juss., Euphorbiaceae (dyer's croton). Rubia tinctorum and Chorozophora tinctoria distributed widely in our study area of West Anatolia were used as the research materials in our study because of their dye value. Aboveground parts of C. tinctoria and underground parts of R. tinctorum were collected from different localities in Western Anatolia for determining their colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 6 publications
0
9
0
2
Order By: Relevance
“…As mentioned in this study, it was concluded that heavy metal accumulation was higher as a result of irrigation with sewage water. Metals in the ground may be accrued directly by wastewater composition or by enhancing the solubility of metals in soil due to the activity of acidification or chelation of used water (Ugulu et al, 2009;Khan et al, 2019d).…”
Section: Metal Accumulation In Water Samplesmentioning
confidence: 99%
“…As mentioned in this study, it was concluded that heavy metal accumulation was higher as a result of irrigation with sewage water. Metals in the ground may be accrued directly by wastewater composition or by enhancing the solubility of metals in soil due to the activity of acidification or chelation of used water (Ugulu et al, 2009;Khan et al, 2019d).…”
Section: Metal Accumulation In Water Samplesmentioning
confidence: 99%
“…C. tinctoria a produces dark blue dye due to its high solubility in water (Ugulu et al. 2009 ) and flavonoid content (Hashim et al. 1990 ).…”
Section: Introductionmentioning
confidence: 99%
“…Uğulu ve ark. [17], farklı yerlerden toplanan Rubia tinctorum ve Chrozophora tinctoria bitkilerinin yün kumaşı boyama özelliklerini renk şiddeti bakımından değerlendirmişler, R. tinctorum bitkisinde 11.01-28.07, C. tinctoria'da ise 3.21-6.40 arasında renk şiddeti değerleri elde etmişlerdir. Yün kumaşların kökboya ile boyandığı bir başka çalışmada, renk şiddeti üzerine farklı mordanların ve boyama yöntemlerinin etkisi incelenmiştir.…”
Section: Introductionunclassified
“…Kızılağaç yaprağı ile yapılan boyamaların K/S renk şiddetleri (pH1 nötr; pH2: yün için pH=4; pamuk için pH=10) Ayva, nar, elma kabuğu, siyah üzüm ve çay yaprağının yün boyama potansiyelini inceleyen Tutak ve Benli[13], FeSO4 mordanı varlığında 9.71-21.84; AlK(SO4)2 mordanı varlığında ise 7.88-13.72 arasında değişen renk şiddeti değerleri elde etmişlerdir. Farklı yerlerden toplanan C. tinctoria ve R. tinctorium bitkilerinin yün boyama kapasitelerini renk şiddeti bakımından değerlendiren Ugulu ve ark [17],. C. tinctoria için 3.21-6.40 arasında, R. tinctorium için ise 11.01-28.07 arasında değerler elde etmişlerdir.…”
unclassified